Strategi Penyelesaian Pembiayaan Akad Murabahah yang Bermasalah di BMT UGT Sidogiri Capem Kraksaan - Hayatul Millah; Moh Nurul Amrullah D (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2019)
The purpose of this research is to find out the strategies used by BMT in resolving the murabahah financing that is problematic at BMT UGT Sidogiri Capem Kraksaan, knowing the factors that are the supporters in carrying out the problem solving financing strategies at BMT UGT Sidogiri Capem Kraksaan, knowing the factors - factors that become obstacles in carrying out financing strategies that are problematic in BMT UGT Sidogiri Capem Kraksaan. The type of research used in this study is qualitative research with a case study approach. The results of this study indicate that the strategy for resolving murabahah financing that is problematic in BMT UGT is by rescheduling, calling customers, giving warning letters (SP) up to 3 times and discussing the next steps that will be taken by both parties, confiscation of collateral . Factors supporting the murabhaah financing settlement strategy that were troubled by BMT UGT Sidogiri Capem Kraksaan were AOA / AOP officers who always communicated, officers, AOP / AOA always supervised customer financing, always approached customers, routinely collected by AOP officers. The inhibiting factor for the problem solving strategy for murabhaah financing at BMT UGT Sidogiri Capem Kraksaan is the AOA / AOP who are not strict in carrying out their duties so customers are negligent in their responsibilities, AOP officers do not routinely collect from customers, officers do not always report things that are a problem in this murabahah financing to the head of BMT UGT Sidogiri, AOA / AOP officers and Head of Sidogiri BMT UGT are not communicating enough, AOA / AOP is slow in responding to troublesome murabahah financing problems carried out by customers.